Distribution, development, transformation characteristics, and hydrate prospect prediction of the rift basins of northwest Zealandia in the Southwest Pacific - Song, Lijun; Feng, Xuliang; Yang, Yushen; Li, Yamin (Frontiers in Earth Science, 2022)
As the last area with unknown oil exploration potential, the Zealandia block has attracted the attention of petroleum scientists. Due to the migrated hydrocarbon gases generated from coal-measure source rocks can form hydrates in shallow seabed, so under the constraint of the known rift distribution, the gravity and magnetic anomaly data are utilized to predict the distribution of rift basins. Combined with the results of seismic interpretation, the balanced cross-section technique and basin simulation technique are utilized to analyze the development law of the rift basins and hydrocarbon generation history of source rocks for the hydrate prospect prediction of the rift basins of Northwest Zealandia. The time of rifting in Zealandia varies greatly from place to place, however the migration of the rifting has obvious regularity. It has experienced extensive rifts, migrated to the east of the Lord Howe Ridge, migrated to the west of the Lord Howe Ridge, migrated to the west of the Dampier Ridge, and finally migrated to the both sides of the Lord Howe Ridge,and then experienced multiple stages of compression transformation and deep burial transformation.For a single rift basin, it can be roughly divided into the volcanic eruption rift I stage, rift Ⅱ stage, rift Ⅲstage, compression transformation stage, stress relaxation subsisdence stage, shear compression deformation stage, and post-rift thermal subsidence stage. The upper Cretaceous coal source rock in the deep part of rift or deeper rift on the eastern side of Lord Howe ridge has entered wet gas generation stage, and the coal-generated wet gas may migrate along the fault and form gas hydrate in the shallow seabed stable zone.